Graphite material, preparation method thereof, negative pole piece containing graphite material, battery and electric device

By using graphite materials with small grain size and small volume changes during the lithium embedding process, the problem of insufficient cycle life of the battery under high energy density is solved, and a longer cycle life and higher energy density is achieved.

CN119833631AActive Publication Date: 2025-04-15CONTEMPORARY AMPEREX TECHNOLOGY CO LTD

Patent Information

Application Number
CN202311677312.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-12-07
Publication Date
2025-04-15
Estimated Expiration
2043-12-07

AI Technical Summary

Technical Problem

It is difficult for existing batteries to achieve longer cycle life under the premise of having a higher energy density.

Method used

A special graphite material is used, which has a small grain size along the c-axis direction during lithium embedding, and the volume changes in the entire lithium embedding process, thereby reducing the lattice expansion of the graphite material during battery charging, reducing the negative electrode-electrolyte interface side reaction and irreversible consumption of lithium ions.

Benefits of technology

By reducing the lattice expansion and the thickness expansion of the negative electrode sheet, the irreversible consumption of lithium ions is reduced, the cycle life of the battery is significantly improved, and the energy density is also high.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119833631A_ABST
    Figure CN119833631A_ABST
Patent Text Reader

Abstract

The invention discloses a graphite material and a preparation method thereof, and a negative pole piece, a battery and an electric device comprising the graphite material. The graphite material satisfies the following conditions: (Lc100% SOC)-Lc0% SOC) / Lc50% SOC is less than or equal to 0.0750, and Lc0% SOC is less than or equal to 50nm. According to the invention, the battery has long cycle life.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to a graphite material and a preparation method thereof, as well as a negative electrode sheet, a battery and an electrical device containing the same. Background Art

[0002] In recent years, batteries have been widely used in the field of energy storage, which has led to higher and higher requirements for battery cycle life. However, how to make batteries have a longer cycle life while having a higher energy density is still a difficulty in current battery development. Summary of the invention

[0003] The present application provides a graphite material and a preparation method thereof, as well as a negative electrode plate, a battery and an electrical device containing the same, which can enable the battery to have a long cycle life.

[0004] In a first aspect, the present application provides a graphite material, wherein the graphite material satisfies (Lc 100%SOC -Lc 0%SOC ) / Lc 50%SOC ≤0.0750, and Lc 0%SOC Less than or equal to 50nm.

[0005] Lc 0%SOC It indicates the grain size of the graphite material along the c-axis direction in the lithium-embedded 0% SOC state, in nm; Lc 50%SOC It indicates the grain size of the graphite material along the c-axis direction when the lithium is inserted into the 50% SOC state, in nm; Lc 100%SOC It represents the grain size of the graphite material along the c-axis direction in the lithium-intercalated 100% SOC state, in nm.

[0006] The graphite material provided in the embodiment of the present application satisfies (Lc 100%SOC -Lc 0%SOC ) / Lc 50%SOC ≤0.0750, and Lc 0%SOC The graphite material has a small grain size along the c-axis direction under the lithium insertion 0% SOC state, and the volume change of the graphite material during the entire lithium insertion process is small, thereby reducing the lattice expansion of the graphite material during battery charging and reducing the thickness expansion of the negative electrode plate, thereby reducing the negative electrode-electrolyte interface side reactions and reducing the irreversible consumption of lithium ions, thereby increasing the cycle life of the battery and meeting the needs of long-life energy storage batteries.

[0007] In some embodiments, 0.0100≤(Lc 100%SOC -Lc 0%SOC ) / Lc 50%SOC ≤0.0750, optionally, 0.0100≤(Lc 100%SOC -Lc0%SOC ) / Lc 50%SOC ≤0.0500. This helps the battery to better combine higher energy density and longer cycle life.

[0008] In some embodiments, 15 nm ≤ Lc 0%SOC ≤47nm, optionally, 25nm≤Lc 0%SOC ≤45nm. The grain size Lc of graphite material along the c-axis direction in the lithium-embedded 0% SOC state 0%SOC When within the above range, the lattice expansion of the graphite material during battery charging can be further reduced, and the thickness expansion of the negative electrode plate can be reduced, thereby further reducing the negative electrode-electrolyte interface side reactions and reducing the irreversible consumption of lithium ions, thereby further improving the cycle life of the battery.

[0009] In some embodiments, 20 nm ≤ Lc 100%SOC ≤60nm, optionally, 28nm≤Lc 100%SOC ≤50nm. The grain size Lc of graphite material along the c-axis direction in the state of 100% SOC of lithium insertion 100%SOC When within the above range, the lattice expansion of the graphite material during battery charging can be further reduced, and the thickness expansion of the negative electrode plate can be reduced, thereby further reducing the negative electrode-electrolyte interface side reactions and reducing the irreversible consumption of lithium ions, thereby further improving the cycle life of the battery.

[0010] In some embodiments, the gram capacity of the graphite material is 280 mAh / g-340 mAh / g, and can be 290 mAh / g-335 mAh / g. When the gram capacity of the graphite material is within the above range, it is beneficial for the battery to have both high energy density and long cycle life.

[0011] In some embodiments, the volume distribution particle size Dv1 of the graphite material is 0.5 μm-3.1 μm, and can be optionally 1 μm-2.5 μm.

[0012] In some embodiments, the volume distribution particle size Dv10 of the graphite material is 3 μm-6.2 μm, and can be optionally 3.2 μm-5 μm.

[0013] In some embodiments, the volume distribution particle size Dv50 of the graphite material is 5 μm-15 μm, and can be optionally 8 μm-12 μm.

[0014] By adjusting the volume distribution particle size of the graphite material, the grain size along the c-axis direction during the lithium insertion process of the graphite material can be reduced, thereby reducing the lattice expansion of the graphite material during battery charging and the thickness expansion of the negative electrode plate, thereby reducing the negative electrode-electrolyte interface side reactions and reducing the irreversible consumption of lithium ions, thereby increasing the cycle life of the battery; it can also increase the lithium insertion channels of the graphite material and reduce lithium deposition.

[0015] In some embodiments, the particle size distribution of the graphite material is (Dv90-Dv10) / Dv50 is 1.02-1.57, and can be optionally 1.11-1.49.

[0016] When the particle size distribution (Dv90-Dv10) / Dv50 of the graphite material is within the above range, the thickness expansion of the negative electrode plate during battery charging can be reduced, thereby reducing the negative electrode-electrolyte interface side reactions, reducing the irreversible consumption of lithium ions, and thus improving the cycle life of the battery.

[0017] In some embodiments, the graphite material has a grain size La along the a-axis direction in the lithium-intercalated 0% SOC state. 0%SOC Less than or equal to 140nm. The grain size La along the a-axis direction of the graphite material in the lithium-embedded 0% SOC state 0%SOC Within the above range, the graphite material has the characteristics of high isotropy and small grain size, so that the graphite material can have more lithium insertion channels, thereby reducing lithium deposition, which is beneficial to improving the cycle life of the battery.

[0018] In some embodiments, the graphitization degree of the graphite material is 70%-88%, and can be 75%-85%. When the graphitization degree of the graphite material is within the above range, on the one hand, the graphite material can have a higher capacity and the battery can have a higher energy density; on the other hand, the grain size along the c-axis direction during the lithium insertion process of the graphite material can be reduced, thereby reducing the lattice expansion of the graphite material during battery charging and reducing the thickness expansion of the negative electrode plate, thereby reducing the negative electrode-electrolyte interface side reactions, reducing the irreversible consumption of lithium ions, and thus improving the cycle life of the battery.

[0019] In some embodiments, the tap density of the graphite material is 1.0 m 3 / g-1.3m 3 When the tap density of the graphite material is within the above range, the compaction density of the negative electrode film layer can be increased, which is conducive to the battery having a higher energy density.

[0020] In some embodiments, the specific surface area of ​​the graphite material is 0.6 m 2 / g-2m 2When the specific surface area of ​​the graphite material is within the above range, the negative electrode-electrolyte interface side reaction can be reduced, and the irreversible consumption of lithium ions can be reduced, thereby improving the cycle life of the battery.

[0021] In some embodiments, the surface of the graphite material further includes a carbon layer.

[0022] In a second aspect, the present application provides a method for preparing a graphite material, comprising the following steps: providing a coke raw material; crushing, shaping and grading the coke raw material to obtain a graphite precursor; placing the obtained graphite precursor in a graphitization furnace for graphitization at a preset temperature and a preset time, and cooling the furnace to obtain a graphite material, wherein the preset temperature is less than 3000°C and the preset time is less than 24h, wherein the graphite material satisfies (Lc 100%SOC -Lc 0%SOC ) / Lc 50%SOC ≤0.0750, and Lc 0%SOC Less than or equal to 50nm; Lc 0%SOC It indicates the grain size of the graphite material along the c-axis direction in the lithium-embedded 0% SOC state, in nm; Lc 50%SOC It indicates the grain size of the graphite material along the c-axis direction when the lithium is inserted into the 50% SOC state, in nm; Lc 100%SOC It represents the grain size of the graphite material along the c-axis direction in the lithium-intercalated 100% SOC state, in nm.

[0023] The graphite material prepared by the preparation method provided in the embodiment of the present application has a smaller grain size along the c-axis direction, and the volume change of the graphite material during the entire lithium insertion process is small, thereby reducing the lattice expansion of the graphite material during battery charging and reducing the thickness expansion of the negative electrode plate, thereby reducing the negative electrode-electrolyte interface side reactions and reducing the irreversible consumption of lithium ions, thereby improving the cycle life of the battery.

[0024] In some embodiments, the graphitization furnace is a continuous graphitization furnace.

[0025] In some embodiments, the preset temperature is 2500°C-2800°C, and can be optionally 2500°C-2750°C.

[0026] In some embodiments, the preset time is 6h-18h, and can be optionally 8h-15h.

[0027] By further adjusting the preset temperature and / or preset time during the graphitization treatment, on the one hand, the lattice expansion of the graphite material during battery charging can be reduced, the thickness expansion of the negative electrode plate can be reduced, the negative electrode-electrolyte interface side reactions can be reduced, the irreversible consumption of lithium ions can be reduced, and the cycle life of the battery can be improved; on the other hand, the graphite material can also have a higher gram capacity, so that the battery can have both a long cycle life and a higher energy density.

[0028] In some embodiments, the coke feedstock includes at least one of petroleum coke and needle coke.

[0029] In some embodiments, the coke raw material is petroleum coke, and based on the total volume of the coke raw material structure, the volume proportion of the mosaic and regional structures in the petroleum coke is greater than or equal to 60%, and can be optionally 65%-80%.

[0030] In some embodiments, the coke raw material is needle coke, and based on the total volume of the coke raw material structure, the volume proportion of the fiber-type structure in the needle coke is 40%-60%, and optionally 45%-55%.

[0031] By selecting the above-mentioned specific type of coke raw material, under the same graphitization treatment conditions, the degree of grain development is slower, which is beneficial to regulating the degree of grain development during the graphitization process, and can also reduce the volume change of the graphite particles prepared thereby during the battery charging and discharging process.

[0032] In some embodiments, the coke raw material further satisfies: a volatile matter content of less than or equal to 10 wt %, an ash content of less than or equal to 0.3 wt %, and a sulfur content of less than or equal to 2 wt %.

[0033] In some embodiments, in the step of crushing, shaping and grading the coke raw material to obtain a graphite precursor, the volume distribution particle size Dv1 of the obtained graphite precursor is greater than or equal to 0.3μm, which can be selected as 0.3μm-1.4μm; and / or, the volume distribution particle size Dv10 of the obtained graphite precursor is greater than or equal to 2.0μm, which can be selected as 2.1μm-4.0μm; and / or, the volume distribution particle size Dv50 of the obtained graphite precursor is 5μm-16μm, which can be selected as 8μm-11μm; and / or, the particle size distribution of the obtained graphite precursor (Dv90-Dv10) / Dv50 is 1.05-1.61, which can be selected as 1.18-1.52.

[0034] By adjusting the volume particle size distribution of the graphite precursor within the above range, the grain size of the graphite material crystal along the c-axis direction can be reduced, the volume expansion of the graphite material during battery charging can be reduced, and the graphite material can also have good dynamic properties.

[0035] In some embodiments, before placing the obtained graphite precursor in a graphitization furnace for graphitization at a preset temperature and a preset time, the method further includes the step of pre-carbonizing the obtained graphite precursor. Optionally, the obtained graphite precursor is heated to 600°C-1100°C at a heating rate of 1°C / min-5°C / min and kept at this temperature for 18h-24h for pre-carbonization.

[0036] In some embodiments, the preparation method further includes the steps of placing the obtained graphite precursor in a graphitization furnace for graphitization treatment at a preset temperature and a preset time, and then screening and demagnetizing to obtain a graphite material.

[0037] In some embodiments, the preparation method further comprises the step of: mixing the obtained graphite material with the coating agent and placing the mixture in a carbonization furnace for carbonization treatment to form a carbon layer on the surface of the graphite material.

[0038] Optionally, the coating agent includes asphalt, and more optionally, the softening point temperature of the asphalt is 150°C-300°C, optionally 200°C-250°C.

[0039] Optionally, the temperature of the carbonization treatment is 950°C-1300°C, optionally 1100°C-1200°C.

[0040] Optionally, the carbonization treatment time is 1h-5h, optionally 2h-3h.

[0041] In a third aspect, the present application provides a negative electrode plate, comprising a negative electrode current collector and a negative electrode film layer located on at least one surface of the negative electrode current collector, wherein the negative electrode film layer comprises the graphite material of the first aspect of the present application or the graphite material prepared by the preparation method of the second aspect of the present application.

[0042] In some embodiments, the compaction density of the negative electrode film layer is 1.15 g / cm 3 -1.55g / cm 3 .

[0043] In some embodiments, the surface density of the negative electrode film layer is 7 mg / cm 2 -15mg / cm 2 .

[0044] In a fourth aspect, the present application provides a battery, comprising the negative electrode plate of the third aspect of the present application.

[0045] In a fifth aspect, the present application provides an electrical device, comprising the battery of the fourth aspect of the present application, wherein the battery is used to provide electrical energy.

[0046] The electric device of the present application includes the battery provided by the present application, and thus has at least the same advantages as the battery. BRIEF DESCRIPTION OF THE DRAWINGS

[0047] In order to more clearly illustrate the technical solutions of the embodiments of the present application, the following briefly introduces the drawings required for use in the embodiments of the present application. Obviously, the drawings described below are only some implementation methods of the present application. For ordinary technicians in this field, other drawings can be obtained based on the drawings without creative work.

[0048] Figure 1 is a schematic diagram of a battery cell provided in some embodiments of the present application.

[0049] Figure 2 It is a schematic diagram of an exploded view of a battery cell provided in some embodiments of the present application.

[0050] Figure 3 is a schematic diagram of a battery module provided in some embodiments of the present application.

[0051] Figure 4 is a schematic diagram of a battery pack provided in some embodiments of the present application.

[0052] Figure 5 yes Figure 4 An exploded diagram of the battery pack is shown.

[0053] Figure 6 It is a schematic diagram of an electrical device provided in some embodiments of the present application.

[0054] In the drawings, the drawings may not be drawn according to the actual scale. The reference numerals are as follows: 1 battery pack, 2 upper box, 3 lower box, 4 battery module, 5 battery cell, 51 housing, 52 electrode assembly, 53 cover plate. DETAILED DESCRIPTION

[0055] Hereinafter, the graphite material and its preparation method, as well as the negative electrode sheet, battery and electric device containing the same are described in detail with appropriate reference to the accompanying drawings to specifically disclose the embodiments of the present application. However, there may be cases where unnecessary detailed descriptions are omitted. For example, there are cases where detailed descriptions of well-known matters and repeated descriptions of actually the same structures are omitted. This is to avoid the following description from becoming unnecessarily lengthy and to facilitate the understanding of those skilled in the art. In addition, the drawings and the following descriptions are provided for those skilled in the art to fully understand the present application and are not intended to limit the subject matter described in the claims.

[0056] "Scope" disclosed in the present application is limited in the form of lower limit and upper limit, and a given range is limited by selecting a lower limit and an upper limit, and the selected lower limit and upper limit define the boundary of a special range. The scope limited in this way can be including end values ​​or not including end values, and can be arbitrarily combined, that is, any lower limit can be combined with any upper limit to form a scope. For example, if the scope of 60-120 and 80-110 is listed for a specific parameter, it is understood that the scope of 60-110 and 80-120 is also expected. In addition, if the minimum range values ​​1 and 2 are listed, and if the maximum range values ​​3, 4 and 5 are listed, the following scope can be all expected: 1-3, 1-4, 1-5, 2-3, 2-4 and 2-5. In the present application, unless otherwise specified, the numerical range "ab" represents the abbreviation of any real number combination between a and b, wherein a and b are real numbers. For example, the numerical range "0-5" means that all real numbers between "0-5" are listed in this document, and "0-5" is just an abbreviation of these numerical combinations. In addition, when a parameter is expressed as an integer ≥ 2, it is equivalent to disclosing that the parameter is, for example, an integer of 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, etc.

[0057] If not otherwise specified, all embodiments and optional embodiments of the present application may be combined with each other to form new technical solutions, and such technical solutions should be deemed to be included in the disclosure of the present application.

[0058] Unless otherwise specified, all technical features and optional technical features of the present application may be combined with each other to form new technical solutions, and such technical solutions should be deemed to be included in the disclosure of the present application.

[0059] If there is no special explanation, all steps of the present application can be performed sequentially or randomly, preferably sequentially. For example, the method includes steps (a) and (b), indicating that the method may include steps (a) and (b) performed sequentially, or may include steps (b) and (a) performed sequentially. For example, the method may also include step (c), indicating that step (c) may be added to the method in any order, for example, the method may include steps (a), (b) and (c), or may include steps (a), (c) and (b), or may include steps (c), (a) and (b), etc.

[0060] In the present application, the terms "plurality" and "multiple" refer to two or more.

[0061] Unless otherwise specified, the terms used in this application have the commonly understood meanings that are commonly understood by those skilled in the art.

[0062] Unless otherwise specified, the values ​​of the parameters mentioned in this application can be measured by various test methods commonly used in the art, for example, they can be measured according to the test methods given in the examples of this application. Unless otherwise specified, the test temperature of each parameter is 25°C.

[0063] The battery mentioned in the embodiments of the present application may be a single physical module including one or more battery cells to provide higher voltage and capacity. For example, the battery mentioned in the present application may include a battery cell, a battery module or a battery pack.

[0064] A battery cell is the smallest unit of a battery, which can independently realize the functions of charging and discharging. The battery cell can be cylindrical, rectangular or in other shapes, etc., which is not limited in the embodiments of the present application. Figure 1 The battery cell 5 is a rectangular parallelepiped structure as an example.

[0065] When there are multiple battery cells, the multiple battery cells are connected in series, in parallel, or in mixed connection through a busbar. In some embodiments, the battery may be a battery module; when there are multiple battery cells, the multiple battery cells are arranged and fixed to form a battery module. In some embodiments, the battery may be a battery pack, which includes a box and battery cells, and the battery cells or battery modules are accommodated in the box. In some embodiments, the box may serve as part of the chassis structure of the vehicle. For example, part of the box may become at least a part of the floor of the vehicle, or part of the box may become at least a part of the crossbeam and longitudinal beam of the vehicle.

[0066] In some embodiments, the battery may be an energy storage device, which includes an energy storage container, an energy storage cabinet, and the like.

[0067] A battery cell generally includes an electrode assembly and an electrolyte. The electrode assembly generally includes a positive electrode sheet and a negative electrode sheet. The electrode assembly may be a wound structure or a laminated structure, which is not limited in the present application.

[0068] The battery cell may also include an outer package, which may be used to encapsulate the electrode assembly and the electrolyte. The outer package may be a hard shell, such as a hard plastic shell, an aluminum shell, a steel shell, etc. The outer package may also be a soft package, such as a bag-type soft package. The material of the soft package may be plastic, such as one or more of polypropylene (PP), polybutylene terephthalate (PBT) and polybutylene succinate (PBS).

[0069] In some embodiments, Figure 2As shown, the outer package may include a shell 51 and a cover plate 53. The shell 51 may include a bottom plate and a side plate connected to the bottom plate, and the bottom plate and the side plate enclose a receiving cavity. The shell 51 has an opening connected to the receiving cavity, and the cover plate 53 is used to cover the opening to close the receiving cavity. The electrode assembly 52 is encapsulated in the receiving cavity. The number of electrode assemblies 52 contained in the battery cell 5 can be one or more, which can be adjusted according to demand.

[0070] In some embodiments, battery cells may be assembled into a battery module. The battery module may contain multiple battery cells, and the specific number may be adjusted according to the application and capacity of the battery module. Figure 3 FIG. 4 is a schematic diagram of a battery module 4 as an example. Figure 3 As shown, in the battery module 4, the plurality of battery cells 5 may be arranged in sequence along the length direction of the battery module 4. Of course, they may also be arranged in any other manner. Further, the plurality of battery cells 5 may be fixed by fasteners.

[0071] Optionally, the battery module 4 may further include a housing having a receiving space, and the plurality of battery cells 5 are received in the receiving space.

[0072] In some embodiments, the battery modules described above may also be assembled into a battery pack, and the number of battery modules contained in the battery pack may be adjusted according to the application and capacity of the battery pack.

[0073] Figure 4 and Figure 5 FIG. 1 is a schematic diagram of a battery pack 1 as an example. Figure 4 and Figure 5 As shown, the battery pack 1 may include a box body and a plurality of battery modules 4 disposed in the box body. The box body includes an upper box body 2 and a lower box body 3, and the upper box body 2 is used to cover the lower box body 3 and form a closed space for accommodating the battery modules 4. The plurality of battery modules 4 may be arranged in the box body in any manner.

[0074] The battery provided in the embodiment of the present application may include a lithium-ion battery.

[0075] The graphite material provided in the embodiment of the present application satisfies (Lc 100%SOC -Lc 0%SOC ) / Lc 50%SOC ≤0.0750, and Lc 0%SOC Less than or equal to 50nm.

[0076] Lc 0%SOC Indicates the grain size of graphite material along the c-axis direction in the lithium-embedded 0% SOC state, in nm; Lc 50%SOC It indicates the grain size of graphite material along the c-axis direction when lithium is inserted into 50% SOC state, in nm; Lc100%SOC It indicates the grain size of graphite material along the c-axis direction in the state of 100% lithium insertion SOC, in nm.

[0077] As the battery is charged more, lithium ions continue to embed into the lattice of the graphite material, which will cause the lattice of the graphite material to expand. And as the number of battery cycles increases, the graphite material will experience a large lattice expansion, which will cause a large volume change in the graphite material particles, which will cause the solid electrolyte interface (SEI) film on the surface of the graphite material particles to be repeatedly broken and generated, thereby increasing the negative electrode-electrolyte interface side reactions, increasing the irreversible consumption of lithium ions, and affecting the cycle life of the battery. In addition, the large lattice expansion of the graphite material will also deteriorate the electronic contact between the graphite material particles and the negative electrode current collector, causing some graphite material particles to lose electronic contact and electrochemical activity, which will cause uneven local current at the negative electrode, which will lead to accelerated lithium precipitation and battery capacity decay, reducing the battery's cycle performance.

[0078] The graphite material provided in the embodiment of the present application satisfies (Lc 100%SOC -Lc 0%SOC ) / Lc 50%SOC Greater than 0 and less than or equal to 0.0750, and Lc 0%SOC The graphite material has a smaller grain size along the c-axis direction under the lithium insertion 0% SOC state, and the volume change of the graphite material during the entire lithium insertion process is smaller, thereby reducing the lattice expansion of the graphite material during battery charging, reducing the thickness expansion of the negative electrode plate, thereby reducing the negative electrode-electrolyte interface side reactions, reducing the irreversible consumption of lithium ions, and thus improving the cycle life of the battery, and is conducive to meeting the needs of long-life energy storage batteries.

[0079] Optionally, (Lc 100%SOC -Lc 0%SOC ) / Lc 50%SOC The amount may be 0.0100, 0.0120, 0.0140, 0.0155, 0.0169, 0.0185, 0.0200, 0.0250, 0.0300, 0.0350, 0.0400, 0.0440, 0.0500, 0.0550, 0.0600, 0.0650, 0.0700, 0.0750, or a range consisting of any of the above values.

[0080] Optionally, in some embodiments, 0.0100≤(Lc 100%SOC -Lc 0%SOC ) / Lc 50%SOC ≤0.0750,0.0100≤(Lc 100%SOC -Lc 0%SOC ) / Lc 50%SOC≤0.0500. This helps the battery to better combine higher energy density and longer cycle life.

[0081] In some embodiments, 15 nm ≤ Lc 0%SOC ≤47nm, optionally, 25nm≤Lc 0%SOC ≤45nm.

[0082] The grain size Lc of graphite material along the c-axis direction in the lithium-intercalated 0% SOC state 0%SOC When within the above range, the lattice expansion of the graphite material during battery charging can be further reduced, and the thickness expansion of the negative electrode plate can be reduced, thereby further reducing the negative electrode-electrolyte interface side reactions and reducing the irreversible consumption of lithium ions, thereby further improving the cycle life of the battery.

[0083] In some embodiments, 20 nm ≤ Lc 100%SOC ≤60nm, optionally, 28nm≤Lc 100%SOC ≤50nm.

[0084] The grain size Lc of graphite material along the c-axis direction under 100% SOC state of lithium insertion 100%SOC When within the above range, the lattice expansion of the graphite material during battery charging can be further reduced, and the thickness expansion of the negative electrode plate can be reduced, thereby further reducing the negative electrode-electrolyte interface side reactions and reducing the irreversible consumption of lithium ions, thereby further improving the cycle life of the battery.

[0085] In some embodiments, the grain size La of the graphite material along the a-axis direction in the lithium-intercalated 0% SOC state is 0%SOC It can be greater than 0 and less than or equal to 140nm.

[0086] The grain size La of graphite material along the a-axis direction under lithium insertion 0% SOC state 0%SOC Within the above range, the graphite material has the characteristics of high isotropy and small grain size, so that the graphite material can have more lithium insertion channels, thereby reducing lithium deposition, which is beneficial to improving the cycle life of the battery.

[0087] In some embodiments, the gram capacity of the graphite material may be 280 mAh / g-340 mAh / g, and optionally 290 mAh / g-335 mAh / g.

[0088] When the gram capacity of the graphite material is within the above range, it is beneficial for the battery to have both higher energy density and longer cycle life.

[0089] In some embodiments, the graphitization degree of the graphite material may be 70%-88%, and optionally 75%-85%.

[0090] When the graphitization degree of the graphite material is within the above range, on the one hand, the graphite material can have a higher capacity and the battery can have a higher energy density; on the other hand, the grain size along the c-axis direction during the lithium insertion process of the graphite material can be reduced, thereby reducing the lattice expansion of the graphite material during battery charging and reducing the thickness expansion of the negative electrode plate, thereby reducing the negative electrode-electrolyte interface side reactions, reducing the irreversible consumption of lithium ions, and thus improving the cycle life of the battery.

[0091] In some embodiments, the graphite material is in the form of primary particles.

[0092] In some embodiments, the volume distribution particle size Dv1 of the graphite material may be 0.5 μm-3.1 μm, and may be 1 μm-2.5 μm.

[0093] In some embodiments, the volume distribution particle size Dv10 of the graphite material may be 3 μm-6.2 μm, and may be 3.2 μm-5 μm.

[0094] In some embodiments, the volume distribution particle size Dv50 of the graphite material may be 5 μm-15 μm, and may be 8 μm-12 μm.

[0095] By adjusting the volume distribution particle size of the graphite material, the grain size along the c-axis direction during the lithium insertion process of the graphite material can be reduced, thereby reducing the lattice expansion of the graphite material during battery charging and the thickness expansion of the negative electrode plate, thereby reducing the negative electrode-electrolyte interface side reactions and reducing the irreversible consumption of lithium ions, thereby increasing the cycle life of the battery; it can also increase the lithium insertion channels of the graphite material and reduce lithium deposition.

[0096] In some embodiments, the particle size distribution of the graphite material (Dv90-Dv10) / Dv50 may be 1.02-1.57, and may be optionally 1.11-1.49.

[0097] When the particle size distribution (Dv90-Dv10) / Dv50 of the graphite material is within the above range, the thickness expansion of the negative electrode plate during battery charging can be reduced, thereby reducing the negative electrode-electrolyte interface side reactions, reducing the irreversible consumption of lithium ions, and thus improving the cycle life of the battery. When the particle size distribution (Dv90-Dv10) / Dv50 of the graphite material is large, the fine powder content in the graphite material is high, which will increase the irreversible capacity loss during the battery cycle, thereby reducing the cycle life of the battery. When the particle size distribution (Dv90-Dv10) / Dv50 of the graphite material is small, the repeated charging and discharging of the graphite particles during the battery cycle causes the graphite particles to repeatedly expand and contract, and then some graphite particles may be displaced, resulting in an increase in the gaps between the graphite particles; in addition, when the particle size distribution (Dv90-Dv10) / Dv50 of the graphite material is small, the content of fine powder in the graphite material is small, and the graphite particles may be out of electrical contact due to the lack of small fine powder to fill the gaps between the graphite particles, which may lead to rapid decay of the cycle capacity in the later stage of battery use.

[0098] In some embodiments, the tap density of the graphite material may be 1.0 m 3 / g-1.3m 3 / g.

[0099] When the tap density of the graphite material is within the above range, the compaction density of the negative electrode film layer can be improved, which is conducive to the battery having a higher energy density.

[0100] In some embodiments, the specific surface area of ​​the graphite material can be 0.6 m 2 / g-2m 2 / g.

[0101] When the specific surface area of ​​the graphite material is within the above range, the negative electrode-electrolyte interface side reactions can be reduced, and the irreversible consumption of lithium ions can be reduced, thereby increasing the cycle life of the battery.

[0102] In some embodiments, the surface of the graphite material may further include a carbon layer. Optionally, the carbon layer may include one or more of soft carbon and hard carbon.

[0103] The grain size Lc of the graphite material along the c-axis direction or the grain size La along the a-axis direction are both well-known in the art and can be tested using instruments and methods known in the art. For example, an X-ray diffractometer (such as Bruker D8 Discover) can be used for testing. The test can refer to JIS K 0131-1996 and JB / T 4220-2011 to obtain the half-peak width FWHM (002) and FWHM (110) of the 002 and 110 crystal planes in the crystal structure of the graphite material and the crystal plane diffraction peaks Pos (002) and Pos (100), and then the crystal Lc and La values ​​are calculated by the Scherrer formula, where π represents the pi constant.

[0104] Lc=0.89*0.15405*180 / FWHM(002) / π / Cos [Pos(002) * π * 2 / 180] .

[0105] La=1.84*0.15405*180 / FWHM(110) / π / Cos [Pos(110) * π * 2 / 180] .

[0106] Lc 0%SOC , Lc 50%SOC , Lc 100%SOC They represent the grain size of graphite material along the c-axis direction under different lithium insertion states, that is, the height along the c-axis direction. 0%SOC , Lc 50%SOC , Lc 100%SOC All of these can be obtained by testing graphite materials in different lithium insertion states using the above test methods.

[0107] La 0%SOC It indicates the grain size of graphite material along the a-axis direction in the state of 0% SOC of lithium insertion. 0%SOC It can be obtained by the above test method.

[0108] During testing, the negative electrode sheet containing the graphite material provided in the embodiment of the present application can be made into a button battery. For example, the negative electrode sheet containing the graphite material provided in the embodiment of the present application and a lithium metal sheet (as a counter electrode) can be assembled into a button battery.

[0109] The electrolyte of the button battery can be prepared as follows: in an argon atmosphere glove box with a water content of less than 10 ppm, dimethyl carbonate (DMC), ethyl methyl carbonate (EMC), and ethylene carbonate (EC) are mixed in a mass ratio of 1:1:1 to obtain an organic solvent, and then LiPF6 is dissolved in the above organic solvent to prepare an electrolyte with a concentration of 1.0 mol / L.

[0110] The isolation film of the button cell can be a polypropylene (PP) film, and the thickness can be 12 μm.

[0111] The assembly process of the button cell can adopt the technology known in the art, for example, it can be assembled from the positive electrode shell from bottom to top, or it can be assembled from the negative electrode shell from bottom to top, and the entire assembly process is carried out in an argon atmosphere glove box with a water content of less than 10 ppm.

[0112] At 25°C, the prepared button battery was left standing for 6 hours, then discharged at a constant current of 0.15 mA to 5.0 mV; left standing for 5 minutes, and then continued to be discharged at a constant current of 50 μA to 5.0 mV; then charged at a constant current of 0.30 mA to 2 V, at which time the charging capacity was recorded as C0; then the negative electrode was disassembled from the button battery and tested by an X-ray diffractometer to obtain Lc 0%SOC and La 0%SOC .

[0113] At 25°C, the prepared button battery was left standing for 6 hours, then discharged at a constant current of 0.15 mA to 5.0 mV; left standing for 5 minutes, and then continued to discharge at a constant current of 50 μA to 5.0 mV; then charged at a constant current of 0.30 mA to 2 V, at which time the charging capacity was recorded as C0; then discharged at a constant current of 0.05 C0 for 10 hours; then the negative electrode was disassembled from the button battery and tested by an X-ray diffractometer to obtain Lc 50%SOC .

[0114] At 25°C, the prepared button battery was left standing for 6 hours, then discharged at a constant current of 0.15 mA to 5.0 mV; left standing for 5 minutes, and then continued to discharge at a constant current of 50 μA to 5.0 mV; then charged at a constant current of 0.30 mA to 2 V, at which time the charging capacity was recorded as C0; then discharged at a constant current of 0.05 C0 for 20 hours; then the negative electrode was disassembled from the button battery and tested by an X-ray diffractometer to obtain Lc 100%SOC .

[0115] For example, the graphite material sample can be fully stirred and mixed with the conductive agent carbon black and the binder polyvinylidene fluoride (PVDF) in a mass ratio of 91.6:1.8:6.6 in an appropriate amount of solvent N-methylpyrrolidone (NMP) to form a uniform negative electrode slurry; the negative electrode slurry is evenly coated on the surface of the negative electrode current collector copper foil and dried and cold pressed; then the metal lithium sheet is used as the counter electrode, the polypropylene (PP) film is used as the isolation membrane, the electrolyte is injected, and the CR2430 button battery is assembled in an argon-protected glove box. The electrolyte formula used is as follows: dimethyl carbonate (DMC), ethyl methyl carbonate (EMC), and ethylene carbonate (EC) are mixed in a mass ratio of 1:1:1 to obtain an organic solvent, and then LiPF6 is dissolved in the above organic solvent to prepare an electrolyte with a concentration of 1.0 mol / L. The compacted density of the negative electrode sheet can be 1.3g / cm 3 -1.5g / cm 3 .

[0116] At 25°C, the button cell prepared above was first discharged at a constant current of 0.05C to 0.005V, then discharged at a constant current of 10μA to 0.005V, and left to stand for 5 minutes, and the first cycle discharge capacity of the button cell was recorded; then, the button cell was charged at a constant current of 0.1C to 2.0V, and the first cycle charge capacity of the button cell was recorded. The ratio of the first cycle charge capacity of the button cell to the mass of the graphite material sample is the gram capacity of the graphite material.

[0117] The graphitization degree of graphite material is well known in the art and can be tested using instruments and methods known in the art. For example, an X-ray diffractometer (such as Bruker D8 Discover) can be used for testing. The test can refer to JIS K0131-1996 and JB / T 4220-2011 to obtain the average interlayer spacing d of the (002) crystal plane in the crystal structure of the graphite material. 002 Then according to the formula g = (0.344-d 002 ) / (0.344-0.3354)×100% to calculate the graphitization degree. In the above formula, d 002 It is the average interlayer spacing of the (002) crystal plane in the crystal structure of graphite material expressed in nanometers (nm).

[0118] In X-ray diffraction analysis, a copper target can be used as the anode target, and CuKα rays can be used as the radiation source. The scanning 2θ angle range may be 15°-75°, and the scanning rate may be 4° / min.

[0119] The volume distribution particle sizes Dv1, Dv10, Dv50, and Dv90 of materials (such as graphite materials, graphite precursors described below, etc.) are well known in the art, and they represent the particle sizes corresponding to the cumulative volume distribution percentages of the materials reaching 1%, 10%, 50%, and 90%, respectively, and can be measured using instruments and methods known in the art. For example, it can be conveniently measured using a laser particle size analyzer with reference to the particle size distribution laser diffraction method of GB / T19077-2016. The test instrument can be a Mastersizer 3000 laser particle size analyzer from Malvern Instruments Ltd., UK.

[0120] The tap density of graphite material is well known in the art and can be measured using instruments and methods known in the art. For example, it can be measured using a powder tap density tester in accordance with GB / T 5162-2006. The test instrument can be Dandong Better BT-301.

[0121] The specific surface area of ​​graphite material is a well-known meaning in the art and can be measured by instruments and methods known in the art. For example, it can be tested by nitrogen adsorption specific surface area analysis test method according to GB / T 19587-2017 and calculated by BET (Brunauer Emmett Teller) method, wherein the nitrogen adsorption specific surface area analysis test can be performed by Tri-Star 3020 specific surface area pore size analysis tester of Micromeritics, USA.

[0122] The embodiment of the present application also provides a method for preparing the above-mentioned graphite material.

[0123] The preparation method comprises the following steps: providing coke raw material; crushing, shaping and grading the coke raw material to obtain a graphite precursor; placing the obtained graphite precursor in a graphitization furnace for graphitization at a preset temperature and a preset time, and cooling the furnace to obtain a graphite material, wherein the preset temperature is less than 3000°C and the preset time is less than 24h. The graphite material satisfies (Lc 100%SOC -Lc 0%SOC ) / Lc 50%SOC ≤0.0750, and Lc 0%SOC Less than or equal to 50nm; Lc 0%SOC Indicates the grain size of graphite material along the c-axis direction in the lithium-embedded 0% SOC state, in nm; Lc 50%SOC It indicates the grain size of graphite material along the c-axis direction when lithium is inserted into 50% SOC state, in nm; Lc 100%SOC It indicates the grain size of graphite material along the c-axis direction in the state of 100% lithium insertion SOC, in nm.

[0124] By selecting the preset temperature and preset time during graphitization treatment within the above range, the grain size of the graphite material crystal along the c-axis direction can be reduced, the volume expansion of the graphite material during battery charging can be reduced, and the graphite material can also have a higher gram capacity.

[0125] When the preset temperature during graphitization treatment is high and / or the preset time is long, the degree of grain development is better, the grain size of the graphite material crystal along the c-axis direction is larger, and the lattice expansion and volume expansion of the graphite material during the battery charging process are large, which will cause repeated breakage and generation of the SEI film, which is not conducive to improving the cycle life of the battery.

[0126] Therefore, the graphite material prepared by the preparation method provided in the embodiment of the present application has a smaller grain size along the c-axis direction, and the volume change of the graphite material during the entire lithium insertion process is small, thereby reducing the lattice expansion of the graphite material during battery charging and reducing the thickness expansion of the negative electrode plate, thereby reducing the negative electrode-electrolyte interface side reactions and reducing the irreversible consumption of lithium ions, thereby improving the cycle life of the battery.

[0127] In some embodiments, when the obtained graphite precursor is placed in a graphitization furnace for graphitization treatment at a preset temperature and a preset time, the preset temperature may be 2500°C-2800°C, and may be optionally 2500°C-2750°C.

[0128] In some embodiments, when the obtained graphite precursor is placed in a graphitization furnace and graphitized at a preset temperature and a preset time, the preset time may be 6h-18h, and may be optionally 8h-15h.

[0129] By further adjusting the preset temperature and / or preset time during the graphitization treatment, on the one hand, the lattice expansion of the graphite material during battery charging can be reduced, the thickness expansion of the negative electrode plate can be reduced, the negative electrode-electrolyte interface side reactions can be reduced, the irreversible consumption of lithium ions can be reduced, and the cycle life of the battery can be improved; on the other hand, the graphite material can also have a higher gram capacity, so that the battery can have both a long cycle life and a higher energy density.

[0130] In some embodiments, the cooling time may be less than or equal to 5 hours, thereby reducing the surface oxidation problem of the graphite material and improving the performance of the graphite material.

[0131] In some embodiments, the furnace temperature may be less than or equal to 250° C. This can reduce the surface oxidation problem of the graphite material during the furnace transfer process, thereby improving the performance of the graphite material.

[0132] In some embodiments, the coke feedstock may include at least one of petroleum coke and needle coke.

[0133] In the present application, the term "petroleum coke" refers to coke formed by high-temperature carbonization of petroleum residue or petroleum asphalt.

[0134] In the present application, the term "needle coke" refers to coal tar pitch or petroleum pitch, which is carbonized in the liquid phase to generate an anisotropic intermediate phase and then subjected to high-temperature carbonization and other processes to generate coke with a needle-like texture.

[0135] In some embodiments, the raw material may include petroleum coke. Petroleum coke has excellent anisotropy, which is conducive to the preparation of graphite materials with low volume expansion and the long cycle life of the battery; at the same time, petroleum coke has high compaction density and high gram capacity, which is conducive to improving the energy density of the battery. In addition, petroleum coke has a wider source and is conducive to industrial production.

[0136] The above-mentioned coke raw material usually includes at least one of mosaic, regional and fiber structures. Usually, based on the morphological characteristics and isochromatic zone size of the coke raw material under a polarizing microscope, the isochromatic zone microstructure with a size less than 30 μm is determined as a mosaic structure, the isochromatic zone microstructure with a size greater than 30 μm is determined as a regional structure, and the anisotropic strip-shaped isochromatic zone is determined as a fiber structure.

[0137] In some embodiments, the coke raw material may be petroleum coke, and based on the total volume of the coke raw material structure, the volume proportion of the mosaic and regional structures in the petroleum coke may be greater than or equal to 60%, and may be optionally 65%-80%.

[0138] In some embodiments, the coke raw material may be needle coke, and based on the total volume of the coke raw material structure, the volume proportion of the fiber structure in the needle coke may be 40%-60%, and optionally 45%-55%.

[0139] By selecting the above-mentioned specific type of coke raw material, under the same graphitization treatment conditions, the degree of grain development is slower, which is beneficial to regulating the degree of grain development during the graphitization process, and can also reduce the volume change of the graphite particles prepared thereby during the battery charging and discharging process.

[0140] In this application, the volume proportion of mosaic, regional and fiber structures in the coke raw material can be tested by methods known in the art. As an example, the raw material can be taken according to GB 1997-89, the raw material crushed to 1mm is mixed, 40g-50g is shrunk, and 4g-5g of 0.07mm-1.0mm grade samples are taken by square hole sieve for film making; powder coke and block coke optical film are prepared according to MT 116.1-86, the diameter of the powder coke optical film shall not be less than 22mm, and the volume occupied by the cement shall be less than 1 / 3; the sample is placed on a slide with clay, flattened, and then placed on the stage for aligning, and the polarizer and analyzer are adjusted to be orthogonal after the microscope is calibrated. Insert the azurite inspection plate (1λ) so that the field of view presents the interference color of primary red; determine the step length of the moving ruler to ensure that more than 400 effective measuring points are evenly distributed, and the point spacing is 0.3mm-0.5mm, and the line spacing is generally 0.5mm-0.8mm. Starting from one end of the sample, determine the type of microstructure under the intersection of the crosshairs, and divide the number of effective measuring points of the mosaic-type, regional-type or fiber-type optical structure by the total number of testing points as the volume proportion of each structure in the raw material.

[0141] In some embodiments, the coke raw material may also satisfy the following requirements: volatile matter content is less than or equal to 10 wt %, ash content is less than or equal to 0.3 wt %, and sulfur content is less than or equal to 2 wt %.

[0142] In some embodiments, in the step of crushing the coke raw material, a crusher, such as a jaw crusher, can be used to crush the coke raw material. For example, the coke raw material can be crushed to 2mm-5mm and then sieved, such as a 3-20 mesh screen.

[0143] By crushing the coke raw material, the grain size of the graphite material crystal along the c-axis direction can be reduced, and the volume expansion of the graphite material during battery charging can be reduced.

[0144] In some embodiments, in the step of shaping the coke raw material, a shaping machine can be used to shape the crushed coke raw material. The shaping process can reduce burrs on the surface of the crushed coke raw material.

[0145] In some embodiments, in the step of classifying the coke raw material, an air flow classifier can be used to classify the shaped coke raw material. Optionally, the induced draft frequency can be greater than or equal to 20 Hz, and the classification frequency can be greater than or equal to 60 Hz. The classification process can reduce the content of large particles and fine powder in the obtained graphite precursor.

[0146] In some embodiments, in the step of crushing, shaping and grading the coke raw material to obtain a graphite precursor, the volume distribution particle size Dv1 of the obtained graphite precursor can be greater than or equal to 0.3 μm, the volume distribution particle size Dv10 can be greater than or equal to 2.0 μm, the volume distribution particle size Dv50 can be 5 μm-16 μm, and the particle size distribution (Dv90-Dv10) / Dv50 can be 1.05-1.61.

[0147] Optionally, the volume distribution particle size Dv1 of the obtained graphite precursor may be 0.3 μm-1.7 μm, and optionally 0.3 μm-1.4 μm.

[0148] Optionally, the volume distribution particle size Dv10 of the obtained graphite precursor may be 2.1 μm-4.5 μm, and optionally 2.1 μm-4.0 μm.

[0149] Optionally, the volume distribution particle size Dv50 of the obtained graphite precursor may be 8 μm-11 μm.

[0150] Optionally, the particle size distribution (Dv90-Dv10) / Dv50 of the obtained graphite precursor may be 1.18-1.52.

[0151] By adjusting the volume particle size distribution of the graphite precursor within the above range, the grain size of the graphite material crystal along the c-axis direction can be reduced, the volume expansion of the graphite material during battery charging can be reduced, and the graphite material can also have good dynamic properties.

[0152] In some embodiments, the graphitization furnace may be a continuous graphitization furnace.

[0153] In some embodiments, before placing the obtained graphite precursor in a graphitization furnace for graphitization treatment at a preset temperature and a preset time, the preparation method further includes the step of: pre-carbonizing the obtained graphite precursor.

[0154] Optionally, the obtained graphite precursor may be heated to 600° C.-1100° C. at a heating rate of 1° C. / min-5° C. / min and kept at this temperature for 18 h-24 h for pre-carbonization treatment.

[0155] In some embodiments, the preparation method further includes the steps of placing the obtained graphite precursor in a graphitization furnace for graphitization treatment at a preset temperature and a preset time, and then screening and demagnetizing to obtain a graphite material.

[0156] Screening can reduce the content of large particles and fine powder in the finished graphite material, which is conducive to adjusting the particle size and volume particle size distribution of the finished graphite material, thereby reducing the grain size of the graphite material crystal along the c-axis direction and reducing the volume expansion of the graphite material during battery charging. Demagnetization can reduce the content of magnetic impurities in the finished graphite material, which will increase the self-discharge of the battery and reduce the battery performance.

[0157] In some embodiments, the preparation method may further include the steps of: adding the graphite material obtained after graphitization treatment and the coating agent into a high-speed fusion machine for fusion treatment to obtain an intermediate; then placing the intermediate in a carbonization furnace for carbonization treatment to carbonize the coating agent and form a carbon layer on the surface of the graphite material.

[0158] Optionally, the frequency of the fusion processing may be 20 Hz-40 Hz, optionally 30 Hz-38 Hz.

[0159] Optionally, the fusion treatment time may be 5 min-15 min, optionally 8 min-12 min.

[0160] Optionally, the coating agent may include asphalt.

[0161] Optionally, the softening point temperature of the asphalt may be 150°C-300°C, optionally 200°C-250°C.

[0162] Optionally, the temperature of the carbonization treatment may be 950°C-1300°C, optionally 1100°C-1200°C.

[0163] Optionally, the carbonization treatment time may be 1 h-5 h, optionally 2 h-3 h.

[0164] Optionally, the fusion process may be performed twice. During the first fusion process, no coating agent is added to the high-speed fusion machine; during the second fusion process, a coating agent is added to the high-speed fusion machine.

[0165] In some embodiments, the preparation method comprises the following steps: providing a coke raw material, the coke raw material comprises petroleum coke, and based on the total volume of the coke raw material structure, the volume proportion of the mosaic and regional structures in the petroleum coke is greater than or equal to 60%, and can be selected from 65% to 80%; crushing, shaping and grading the coke raw material to obtain a graphite precursor, wherein the volume distribution particle size Dv1 of the obtained graphite precursor is greater than or equal to 0.3 μm, and can be selected from 0.3 μm to 1.4 μm, and the obtained graphite precursor The volume distribution particle size Dv10 of the obtained graphite precursor is greater than or equal to 2.0 μm, and can be selected from 2.1 μm to 4.0 μm. The volume distribution particle size Dv50 of the obtained graphite precursor is 5 μm to 16 μm, and can be selected from 8 μm to 11 μm. The particle size distribution (Dv90-Dv10) / Dv50 of the obtained graphite precursor is 1.05-1.61, and can be selected from 1.40-1.52. The obtained graphite precursor is heated to 600°C-11 at a heating rate of 1°C / min-5°C / min. 00℃ and keep it warm for 18h-24h for pre-carbonization treatment; the pre-carbonized material is graphitized in a continuous graphitization furnace at a preset temperature and preset time, and after cooling, it is taken out of the furnace to obtain a graphitized product. The preset temperature is 2500℃-2800℃, which can be optionally 2500℃-2750℃, and the preset time is 6h-18h, which can be optionally 8h-15h; the obtained graphitized product is sieved and demagnetized to obtain an intermediate product; the sieved and demagnetized intermediate product and the coating agent are added to a high-speed fusion machine for fusion The intermediate is obtained by fusion treatment, the fusion treatment time is 5min-15min, and can be 8min-12min, and the fusion treatment frequency is 20Hz-40Hz, and can be 30Hz-38Hz; the intermediate after fusion treatment is placed in a carbonization furnace for carbonization treatment, the carbonization temperature is 950℃-1300℃, and can be 1100℃-1200℃, and the carbonization time is 1h-5h, and can be 2h-3h; and the final graphite material is obtained after the finished product screening, demagnetization and mixed batch process. The graphite material meets (Lc 100%SOC -Lc 0%SOC ) / Lc 50%SOC ≤0.0750, and Lc 0%SOC Less than or equal to 50nm.

[0166] In some embodiments, the preparation method comprises the following steps: providing a coke raw material, the coke raw material comprises needle coke, and based on the total volume of the coke raw material structure, the volume proportion of the fiber-type structure in the needle coke is 40%-60%, and can be 45%-55%; crushing, shaping and grading the coke raw material to obtain a graphite precursor, and the volume distribution particle size Dv1 of the obtained graphite precursor is greater than or equal to 0.3 μm, and can be 0.3 μm-1.4 μm, and the volume distribution particle size of the obtained graphite precursor is greater than or equal to 0.3 μm, and can be 0.3 μm-1.4 μm. The volume distribution particle size Dv10 is greater than or equal to 2.0 μm, and can be selected from 2.1 μm to 4.0 μm. The volume distribution particle size Dv50 of the obtained graphite precursor is 5 μm to 16 μm, and can be selected from 8 μm to 11 μm. The particle size distribution (Dv90-Dv10) / Dv50 of the obtained graphite precursor is 1.05-1.61, and can be selected from 1.18-1.40. The obtained graphite precursor is heated to 600°C to 1100°C at a heating rate of 1°C / min to 5°C / min. ℃ and keep warm for 18h-24h for pre-carbonization treatment; the pre-carbonized material is graphitized in a continuous graphitization furnace at a preset temperature and preset time, and after cooling, it is taken out of the furnace to obtain a graphitized product. The preset temperature is 2500℃-2800℃, which can be 2500℃-2750℃, and the preset time is 6h-18h, which can be 8h-15h; the obtained graphitized product is sieved and demagnetized to obtain an intermediate product; the sieved and demagnetized intermediate product and the coating agent are added to a high-speed fusion machine for fusion The intermediate is obtained by fusion treatment, the fusion treatment time is 5min-15min, and can be 8min-12min, and the fusion treatment frequency is 20Hz-40Hz, and can be 30Hz-38Hz; the intermediate after fusion treatment is placed in a carbonization furnace for carbonization treatment, the carbonization temperature is 950℃-1300℃, and can be 1100℃-1200℃, and the carbonization time can be 1h-5h, and can be 2h-3h; after the finished product screening, demagnetization and mixed batch process, the final graphite material is obtained. The graphite material meets (Lc 100%SOC -Lc 0%SOC ) / Lc 50%SOC ≤0.0750, and Lc 0%SOC Less than or equal to 50nm.

[0167] [Negative electrode]

[0168] The battery cell includes a negative electrode plate.

[0169] The negative electrode sheet includes a negative electrode current collector and a negative electrode film layer disposed on at least one surface of the negative electrode current collector. For example, the negative electrode current collector has two surfaces opposite to each other in its thickness direction, and the negative electrode film layer is disposed on any one or both of the two opposite surfaces of the negative electrode current collector.

[0170] The negative electrode film layer includes a negative electrode active material. The negative electrode active material includes the above graphite material or the graphite material prepared by the above method.

[0171] In some embodiments, the negative electrode active material may also include other materials known in the art, for example, other materials include but are not limited to one or more of natural graphite, soft carbon, hard carbon, silicon-based materials, tin-based materials, and lithium titanate.

[0172] In some embodiments, the negative electrode film layer may further optionally include a negative electrode conductive agent. As an example, the negative electrode conductive agent may include, but is not limited to, one or more of superconducting carbon, conductive graphite, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene, and carbon nanofibers.

[0173] In some embodiments, the negative electrode film layer may further optionally include a negative electrode binder. As an example, the negative electrode binder may include, butadiene styrene rubber (SBR), water-soluble unsaturated resin SR-1B, water-based acrylic resin (e.g., polyacrylic acid PAA, polymethacrylic acid PMAA, sodium polyacrylate PAAS), polyacrylamide (PAM), polyvinyl alcohol (PVA), sodium alginate (SA), carboxymethyl chitosan (CMCS) or more.

[0174] In some embodiments, the negative electrode film layer may further include other additives. As an example, the other additives may include but are not limited to thickeners, such as sodium carboxymethyl cellulose (CMC), PTC thermistor materials, and the like.

[0175] In some embodiments, the compaction density of the negative electrode film layer can be 1.15 g / cm 3 -1.55g / cm 3 The compaction density of the negative electrode film layer refers to the compaction density of the negative electrode film layer on one side of the negative electrode current collector.

[0176] In some embodiments, the surface density of the negative electrode film layer can be 7 mg / cm 2 -15mg / cm 2 The surface density of the negative electrode film layer refers to the surface density of the negative electrode film layer on one side of the negative electrode current collector.

[0177] The surface density of the negative electrode film layer is well known in the art and can be tested by methods known in the art. For example, a negative electrode sheet coated on one side and cold pressed can be taken (if it is a negative electrode sheet coated on both sides, the negative electrode film layer on one side can be wiped off first), punched into small discs with an area of ​​S1, weighed, and recorded as M1. Then wipe off the negative electrode film layer of the weighed negative electrode sheet, weigh the mass of the negative electrode current collector, and record it as M0. The surface density of the negative electrode film layer = (M1-M0) / S1.

[0178] The compaction density of the negative electrode film layer is well known in the art and can be tested by methods known in the art. The compaction density of the negative electrode film layer = the surface density of the negative electrode film layer / the thickness of the negative electrode film layer. The thickness of the negative electrode film layer is well known in the art and can be tested by methods known in the art, for example, a micrometer can be used for testing.

[0179] The negative electrode film layer is usually formed by coating the negative electrode slurry on the negative electrode current collector, drying and cold pressing. The negative electrode slurry is usually formed by dispersing the negative electrode active material, optional conductive agent, optional binder, and other optional auxiliary agents in a solvent and stirring them uniformly. The solvent can be N-methylpyrrolidone (NMP) or deionized water, but is not limited thereto.

[0180] The negative electrode plate does not exclude other additional functional layers besides the negative electrode film layer. For example, in some embodiments, the negative electrode plate may also include a conductive primer layer (e.g., composed of a conductive agent and a binder) sandwiched between the negative electrode current collector and the negative electrode film layer and disposed on the surface of the negative electrode current collector; in some embodiments, the negative electrode plate may also include a protective layer covering the surface of the negative electrode film layer.

[0181] In some embodiments, the negative electrode current collector may include a metal foil, a three-dimensional porous current collector, or a composite current collector. As an example of a metal foil, copper foil, copper alloy foil, nickel foil, nickel alloy foil, aluminum foil, and aluminum alloy foil may be used. As an example of a three-dimensional porous current collector, copper mesh, nickel mesh, foam copper, foam nickel, and foam aluminum may be used. The composite current collector may include a polymer material base layer and a metal material layer formed on at least one surface of the polymer material base layer. As an example, the metal material may include, but is not limited to, one or more of copper, copper alloy, nickel, nickel alloy, titanium, titanium alloy, aluminum, aluminum alloy, silver, and silver alloy. As an example, the polymer material base layer may include, but is not limited to, one or more of polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene (PS), and polyethylene (PE).

[0182] [Positive electrode]

[0183] The battery cell includes a positive electrode plate.

[0184] The positive electrode sheet includes a positive electrode current collector and a positive electrode film layer disposed on at least one surface of the positive electrode current collector. For example, the positive electrode current collector has two surfaces opposite to each other in its thickness direction, and the positive electrode film layer is disposed on any one or both of the two opposite surfaces of the positive electrode current collector.

[0185] The positive electrode film layer includes a positive electrode active material. For example, the positive electrode active material may include, but is not limited to, one or more of lithium transition metal oxides, lithium-containing phosphates, and their respective modified compounds.

[0186] In some embodiments, the positive electrode active material may include one or more of lithium-containing phosphates and modified compounds thereof, thereby further improving the cycle life of the battery.

[0187] As examples, the lithium transition metal oxide may include, but is not limited to, one or more of lithium cobalt oxide, lithium nickel oxide, lithium manganese oxide, lithium nickel cobalt oxide, lithium manganese cobalt oxide, lithium nickel manganese oxide, lithium nickel cobalt manganese oxide, lithium nickel cobalt aluminum oxide, and their respective modified compounds.

[0188] As an example, the lithium-containing phosphate may include, but is not limited to, one or more of lithium iron phosphate, a composite material of lithium iron phosphate and carbon, lithium manganese phosphate, a composite material of lithium manganese phosphate and carbon, lithium iron manganese phosphate, a composite material of lithium iron manganese phosphate and carbon, and their respective modified compounds. In the present application, the modified compound of each of the above-mentioned positive electrode active materials may be a doping modification and / or surface coating modification of the positive electrode active material.

[0189] In some embodiments, the positive electrode film layer may also optionally include a positive electrode conductive agent. As an example, the positive electrode conductive agent may include, but is not limited to, one or more of superconducting carbon, conductive graphite, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene, and carbon nanofibers.

[0190] In some embodiments, the positive electrode film layer may also optionally include a positive electrode binder. As an example, the positive electrode binder may include, but is not limited to, polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), vinylidene fluoride-tetrafluoroethylene-propylene terpolymer, vinylidene fluoride-hexafluoropropylene-tetrafluoroethylene terpolymer, tetrafluoroethylene-hexafluoropropylene copolymer, fluorinated acrylic resin, styrene-butadiene rubber (SBR), water-soluble unsaturated resin SR-1B, water-based acrylic resin (e.g., polyacrylic acid PAA, polymethacrylic acid PMAA, sodium polyacrylate PAAS), polyacrylamide (PAM), polyvinyl alcohol (PVA), sodium alginate (SA), carboxymethyl chitosan (CMCS) One or more.

[0191] In some embodiments, the positive electrode current collector may be a metal foil or a composite current collector. As an example of a metal foil, aluminum foil may be used. The composite current collector may include a polymer material base layer and a metal material layer formed on at least one surface of the polymer material base layer. As an example, the metal material may include, but is not limited to, one or more of aluminum, aluminum alloy, nickel, nickel alloy, titanium, titanium alloy, silver, and silver alloy. As an example, the polymer material base layer may include, but is not limited to, one or more of polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene (PS), and polyethylene (PE).

[0192] The positive electrode film layer is usually formed by coating the positive electrode slurry on the positive electrode current collector, drying and cold pressing. The positive electrode slurry is usually formed by dispersing the positive electrode active material, optional conductive agent, optional binder and any other components in a solvent and stirring them uniformly. The solvent can be N-methylpyrrolidone (NMP), but is not limited thereto.

[0193] [Electrolytes]

[0194] The battery cell includes an electrolyte. The present application has no specific restrictions on the type of electrolyte, which can be selected according to needs. For example, the electrolyte can include one or more selected from solid electrolytes and liquid electrolytes (ie, electrolytes).

[0195] In some embodiments, the electrolyte is an electrolyte solution, which includes an electrolyte salt and a solvent.

[0196] In some embodiments, as an example, the electrolyte salt may include, but is not limited to, one or more of lithium hexafluorophosphate (LiPF6), lithium tetrafluoroborate (LiBF4), lithium perchlorate (LiClO4), lithium hexafluoroarsenate (LiAsF6), lithium bis(fluorosulfonyl)imide (LiFSI), lithium bis(trifluoromethanesulfonyl)imide (LiTFSI), lithium trifluoromethanesulfonate (LiTFS), lithium difluorooxalatoborate (LiDFOB), lithium dioxalatoborate (LiBOB), lithium difluorophosphate (LiPO2F2), lithium difluorobis(oxalatophosphate) (LiDFOP), and lithium tetrafluorooxalatophosphate (LiTFOP).

[0197] In some embodiments, the solvent may include, but is not limited to, one or more of an ester solvent, a sulfone solvent, and an ether solvent. As an example, the solvent may include, but is not limited to, one or more of ethylene carbonate (EC), propylene carbonate (PC), ethyl methyl carbonate (EMC), diethyl carbonate (DEC), dimethyl carbonate (DMC), dipropyl carbonate (DPC), methyl propyl carbonate (MPC), ethyl propyl carbonate (EPC), butylene carbonate (BC), methyl formate (MF), methyl acetate (MA), ethyl acetate (EA), propyl acetate (PA), methyl propionate (MP), ethyl propionate (EP), propyl propionate, methyl butyrate (MB), ethyl butyrate (EB), 1,4-butyrolactone (GBL), cyclopentane (SF), dimethyl sulfone (MSM), methyl ethyl sulfone (EMS), and diethyl sulfone (ESE).

[0198] In some embodiments, the electrolyte may also optionally include additives. For example, the additives may include negative electrode film-forming additives, positive electrode film-forming additives, and additives that can improve certain properties of the battery, such as additives that improve battery overcharge performance, additives that improve battery high temperature performance, and additives that improve battery low temperature power performance. Optionally, the additives may include one or more of vinylene carbonate and fluoroethylene carbonate (FEC). Optionally, the mass of the additive does not exceed 5% of the total mass of the electrolyte.

[0199] [Isolation film]

[0200] Battery cells using electrolytes and some battery cells using solid electrolytes also include a separator, which is disposed between the positive electrode sheet and the negative electrode sheet and mainly serves to prevent internal short circuits.

[0201] The present application has no particular limitation on the type of isolation membrane, and any known porous isolation membrane with good chemical stability and mechanical stability can be selected.

[0202] In some embodiments, the material of the isolation membrane may include, but is not limited to, one or more of glass fiber, non-woven fabric, polyethylene (PE), polypropylene (PP) and polyvinylidene fluoride. The isolation membrane may be a single-layer film or a multi-layer composite film. When the isolation membrane is a multi-layer composite film, the materials of each layer are the same or different.

[0203] The preparation method of battery cells is well known. In some embodiments, the positive electrode sheet, the separator, the negative electrode sheet and the electrolyte can be assembled to form a battery cell. As an example, the positive electrode sheet, the separator, and the negative electrode sheet can be formed into an electrode assembly through a winding process and / or a lamination process, and the electrode assembly is placed in an outer package, and the above-mentioned electrolyte is injected after drying. After packaging, standing, formation and other processes, a battery cell is obtained. Multiple battery cells can also be further connected in series, in parallel or in mixed connection to form a battery module. Multiple battery modules can also be connected in series, in parallel or in mixed connection to form a battery pack. In some embodiments, multiple battery cells can also directly form a battery pack.

[0204] Electrical devices

[0205] The embodiment of the present application also provides an electrical device, which includes a battery provided in the embodiment of the present application, and the battery is used to provide electrical energy. The battery can be used as a power source for the electrical device, and can also be used as an energy storage unit for the electrical device. The electrical device can be, but is not limited to, a mobile device (such as a mobile phone, a tablet computer, a laptop computer, etc.), an electric vehicle (such as a pure electric vehicle, a hybrid electric vehicle, a plug-in hybrid electric vehicle, an electric bicycle, an electric scooter, an electric golf cart, an electric truck, etc.), an electric train, a ship and a satellite, an energy storage system, etc.

[0206] The electrical device can select a specific type of battery, such as a battery cell, a battery module or a battery pack, according to its usage requirements.

[0207] Figure 6 Schematic diagram of an electric device as an example. The electric device is a pure electric vehicle, a hybrid electric vehicle, or a plug-in hybrid electric vehicle. In order to meet the requirements of the electric device for high power and high energy density, a battery pack or a battery module may be used.

[0208] As another example, the electric device may be a mobile phone, a tablet computer, a notebook computer, etc. The electric device is usually required to be light and thin, and a battery cell may be used as a power source.

[0209] Example

[0210] The following examples describe the disclosure of the present application in more detail, and these examples are only for illustrative purposes, as it is obvious to those skilled in the art that various modifications and variations can be made within the scope of the disclosure of the present application. Unless otherwise stated, all parts, percentages and ratios reported in the following examples are based on mass, and all reagents used in the examples are commercially available or synthesized according to conventional methods and can be used directly without further treatment, and the instruments used in the examples are commercially available.

[0211] Example 1

[0212] (1) Preparation of negative electrode active materials

[0213] A petroleum coke raw material is provided, wherein the mass content of volatile matter is less than or equal to 10wt%, the mass content of ash is less than or equal to 0.3wt%, the mass content of sulfur is less than or equal to 2wt%, and the following conditions are met: the volume proportion of the mosaic and regional structures is 69%.

[0214] The above petroleum coke raw materials are coarsely crushed, and then the coarsely crushed materials are crushed and sieved, and the sieved materials are shaped and graded. A certain amount of fine powder is removed during the grading process to obtain a precursor. The grading frequency of the airflow classifier is 60Hz, and the induced draft frequency is 20Hz; the volume distribution particle size Dv1 of the obtained precursor is controlled at 0.3μm, the volume distribution particle size Dv10 is controlled at 2.1μm, the volume distribution particle size Dv50 is controlled at 8.5μm, and the particle size distribution (Dv90-Dv10) / Dv50 is controlled at 1.52, and then a pre-carbonization treatment is performed. During the pre-carbonization treatment, the temperature is increased at a heating rate of 5℃ / min. Heat to 950℃ and keep warm for 20h; then the pre-carbonized material is continuously graphitized at 2500℃ for 12h to obtain a graphitized product; the obtained graphitized product is screened and demagnetized to obtain an intermediate product; the intermediate product is subjected to the first fusion treatment in a high-speed fusion machine, and then asphalt is added for the second fusion treatment. The frequency of the fusion treatment is 34Hz, and the time of each fusion treatment is 8min. The mass ratio of the intermediate product to asphalt is 98:2; the fused material is transferred to a carbonization furnace and carbonized at 1150℃ for 2h; finally, after the finished product screening, demagnetization and mixed batch process, the graphite material is obtained. The volume distribution particle size Dv1 of the graphite material is 1.1μm, the volume distribution particle size Dv10 is 4.3μm, the volume distribution particle size Dv50 is 9.5μm, and the particle size distribution (Dv90-Dv10) / Dv50 is 1.49. The primary particle graphite material meets (Lc 100%SOC -Lc 0%SOC ) / Lc 50%SOC It is 0.0169.

[0215] (2) Preparation of negative electrode sheet

[0216] The above graphite material, conductive agent Super P, thickener CMC, and binder SBR were mixed in a mass ratio of 96:1:1.2:1.8, and deionized water was added as a solvent. Then, the mixture was stirred under a vacuum mixer until the system was uniform to obtain negative electrode slurry. The negative electrode slurry was evenly coated on the negative electrode current collector copper foil, and the negative electrode sheet was obtained after drying, cold pressing, and slitting. The compacted density of the negative electrode film layer is 1.30g / cm 3 , surface density is 10.22mg / cm 2 .

[0217] (3) Preparation of positive electrode sheet

[0218] The positive electrode active material lithium iron phosphate, conductive agent Super P, and binder PVDF are mixed in a mass ratio of 97:1:2, and the solvent N-methylpyrrolidone (NMP) is added, and then stirred under the action of a vacuum mixer until the system is uniform to obtain a positive electrode slurry; the positive electrode slurry is evenly coated on the positive electrode current collector aluminum foil, and the positive electrode sheet is obtained after drying, cold pressing, and cutting. The compaction density of the positive electrode film layer is 2.50g / cm 3 , the surface density is 19.51mg / cm 2 .

[0219] (4) Preparation of electrolyte

[0220] In an argon atmosphere glove box with a water content of less than 10 ppm, dimethyl carbonate (DMC), ethyl methyl carbonate (EMC), and ethylene carbonate (EC) are mixed in a mass ratio of 1:1:1 to obtain an organic solvent, and then LiPF6 is dissolved in the above organic solvent to prepare a solution with a concentration of 1.0 mol / L. Finally, vinylene carbonate is added to the above solution in an amount of 2 wt%, based on the total mass of the electrolyte.

[0221] (5) Preparation of isolation membrane

[0222] Polypropylene film is used as the isolation film.

[0223] (6) Preparation of batteries (full batteries)

[0224] The positive electrode sheet, the separator, and the negative electrode sheet are stacked in order, so that the separator is placed between the positive electrode sheet and the negative electrode sheet to play an isolating role, and then they are wound to obtain an electrode assembly; the electrode assembly is placed in an outer package, and after drying, the electrolyte is injected, and the battery is obtained after vacuum packaging, standing, forming, shaping and other processes.

[0225] (7) Preparation of button cells

[0226] A lithium metal sheet is used as a counter electrode and assembled into a button cell with the negative electrode sheet, isolation membrane and electrolyte prepared above.

[0227] Examples 2 to 5 and Comparative Examples 1 to 3

[0228] Except for the different preparation process of the negative electrode active material, the preparation process of the battery is the same as that of Example 1. The specific parameters are shown in Table 1.

[0229] Table 1

[0230]

[0231] Example 6

[0232] The preparation process of the battery is the same as that of Example 1 except that the preparation process of the negative electrode active material is different.

[0233] (1) Preparation of negative electrode active materials

[0234] A needle coke raw material is provided, wherein the volatile matter mass content is less than or equal to 10wt%, the ash mass content is less than or equal to 0.3wt%, the sulfur mass content is less than or equal to 2wt%, and the volume proportion of the fiber-type structure is 53%.

[0235] The above needle coke raw materials are roughly crushed into 2mm-5mm by a crusher and passed through a 3-20 mesh sieve; the small particles after the rough crushing are dried to a moisture content of less than 0.5%, and then the small particles of needle coke are crushed, shaped and classified by a ball mill, and a certain amount of fine powder is removed during the classification process to obtain a precursor, the classification frequency of the air flow classifier is 60Hz, and the induced draft frequency is 20Hz; the volume distribution particle size Dv1 of the obtained precursor is controlled at 0.4μm, the volume distribution particle size Dv10 is controlled at 2.8μm, the volume distribution particle size Dv50 is controlled at 8.2μm, and the particle size distribution (Dv90-Dv10) / Dv50 is controlled at 1.34, and then a pre-carbonization treatment is performed. During the carbonization treatment, the temperature is raised to 950°C at a heating rate of 5°C / min and kept warm for 2 hours; thereafter, the pre-carbonized material is continuously graphitized at 2650°C for 12 hours to obtain a graphitized product; the obtained graphitized product is screened and demagnetized to obtain an intermediate product; the intermediate product is subjected to a first fusion treatment in a high-speed fusion machine, and then asphalt is added for a second fusion treatment, the frequency of the fusion treatment is 34 Hz, the time for each fusion treatment is 8 minutes, and the mass ratio of the intermediate product to asphalt is 98:2; the fused material is transferred to a carbonization furnace for carbonization treatment at 1150°C for 2 hours; finally, after the finished product screening, demagnetization and mixed batching processes, the graphite material is obtained. The graphite material has a volume distribution particle size Dv1 of 1.5 μm, a volume distribution particle size Dv10 of 4.0 μm, a volume distribution particle size Dv50 of 9.2 μm, and a primary particle graphite material with a particle size distribution (Dv90-Dv10) / Dv50 of 1.27, and the graphite material satisfies (Lc 100%SOC -Lc 0%SOC ) / Lc 50%SOC It is 0.0195.

[0236] Example 7 and Comparative Example 4

[0237] Except for the different preparation process of the negative electrode active material, the preparation process of the battery is the same as that of Example 6. The specific parameters are shown in Table 2.

[0238] Table 2

[0239]

[0240] Test Section

[0241] (1) Gram capacity test of graphite material

[0242] The negative electrode active material samples prepared in each embodiment and comparative example were fully stirred and mixed with the conductive agent carbon black and the binder polyvinylidene fluoride (PVDF) in a proper amount of solvent N-methylpyrrolidone (NMP) at a mass ratio of 91.6:1.8:6.6 to form a uniform negative electrode slurry; the negative electrode slurry was evenly coated on the surface of the negative electrode current collector copper foil, dried in an oven, and pressed to 1.3 g / cm using a double-roll cold press. 3 -1.5g / cm 3 The compaction density is set aside; dimethyl carbonate (DMC), ethyl methyl carbonate (EMC) and ethylene carbonate (EC) are mixed in a mass ratio of 1:1:1 to obtain an organic solvent, and then LiPF6 is dissolved in the above organic solvent to prepare an electrolyte with a concentration of 1.0 mol / L; thereafter, a metal lithium sheet is used as a counter electrode and a polypropylene film is used as an isolation membrane to assemble a CR2430 button battery in an argon-protected glove box.

[0243] At 25°C, the button cell prepared above was first discharged at a constant current of 0.05C to 0.005V, then discharged at a constant current of 10μA to 0.005V, and left to stand for 5 minutes, and the first cycle discharge capacity of the button cell was recorded; then, the button cell was charged at a constant current of 0.1C to 2.0V, and the first cycle charge capacity of the button cell was recorded. The ratio of the first cycle charge capacity of the button cell to the mass of the negative electrode active material sample is the gram capacity of the negative electrode active material (i.e., graphite material).

[0244] (2)Lc 0%SOC , Lc 50%SOC , Lc 100%SOC ,La 0%SOC Test

[0245] At 25°C, the button cell prepared in the above test was left standing for 6 hours, then discharged at a constant current of 0.15 mA to 5.0 mV; left standing for 5 minutes, and then continued to be discharged at a constant current of 50 μA to 5.0 mV; then charged at a constant current of 0.30 mA to 2 V, at which time the charging capacity was recorded as C0; then the negative electrode was disassembled from the button cell, tested by an X-ray diffractometer, and Lc was calculated by the Scherrer formula 0%SOC and La 0%SOC .

[0246] At 25°C, the button cell prepared in the above test was left standing for 6 hours, then discharged at a constant current of 0.15 mA to 5.0 mV; left standing for 5 minutes, and then continued to discharge at a constant current of 50 μA to 5.0 mV; then charged at a constant current of 0.30 mA to 2 V, at which time the charging capacity was recorded as C0; then discharged at a constant current of 0.05 C0 for 10 hours; then the negative electrode was disassembled from the button cell, tested by an X-ray diffractometer, and Lc was calculated by the Scherrer formula 50%SOC .

[0247] At 25°C, the button cell prepared in the above test was left standing for 6 hours, then discharged at a constant current of 0.15 mA to 5.0 mV; left standing for 5 minutes, and then continued to discharge at a constant current of 50 μA to 5.0 mV; then charged at a constant current of 0.30 mA to 2 V, at which time the charging capacity was recorded as C0; then discharged at a constant current of 0.05 C0 for 20 hours; then the negative electrode was disassembled from the button cell, tested by an X-ray diffractometer, and Lc was calculated by the Scherrer formula 100%SOC .

[0248] (3) Battery cycle performance test

[0249] At 60°C, the prepared full battery was charged to 3.65V at 1C constant current and discharged to 2.5V at 1C constant current for cyclic charge and discharge test until the discharge capacity of the full battery decayed to 80% of the first cycle discharge capacity. The test was stopped and the number of cycles of the full battery was recorded. The greater the number of cycles of the full battery, the better the cycle stability of the full battery.

[0250] The test results are shown in Tables 3 and 4.

[0251] Table 3

[0252]

[0253] Table 4

[0254]

[0255] From the test results in Table 3 and Table 4, it can be seen that (Lc 100%SOC -Lc 0%SOC ) / Lc 50%SOC ≤0.0750, and Lc 0%SOC Graphite materials with a diameter of 50nm or less have excellent cycle performance. This is because the volume change of graphite materials during the entire lithium insertion process is small, which can reduce the lattice expansion of graphite materials during battery charging and reduce the thickness expansion of the negative electrode sheet, thereby reducing the negative electrode-electrolyte interface side reactions and reducing the irreversible consumption of lithium ions, thereby increasing the cycle life of the battery and meeting the needs of long-life energy storage batteries.

[0256] It should be noted that the present application is not limited to the above-mentioned embodiments. The above-mentioned embodiments are only examples, and the embodiments having the same structure as the technical idea and the same effect as the technical solution of the present application are all included in the technical scope of the present application. In addition, without departing from the scope of the main purpose of the present application, various modifications that can be thought of by those skilled in the art to the embodiments and other methods of combining some of the constituent elements in the embodiments are also included in the scope of the present application.

Claims

1. A graphite material, characterized in that: The graphite material satisfies (Lc 100%SOC -Lc 0%SOC ) / Lc 50%SOC ≤0.0750, and Lc 0%SOC Less than or equal to 50nm; Lc 0%SOC It indicates the grain size of the graphite material along the c-axis direction in the lithium-embedded 0% SOC state, in nm; Lc 50%SOC It indicates the grain size of the graphite material along the c-axis direction when the lithium is inserted into the 50% SOC state, in nm; Lc 100%SOC It represents the grain size of the graphite material along the c-axis direction in the lithium-intercalated 100% SOC state, in nm.

2. The graphite material according to claim 1, characterized in that: 0.0100≤(Lc 100%SOC -Lc 0%SOC ) / Lc 50%SOC ≤0.0750, optionally, 0.0100≤(Lc 100%SOC -Lc 0%SOC ) / Lc 50%SOC ≤0.0500; and / or, 15nm≤Lc 0%SOC ≤47nm, optionally, 25nm≤Lc 0%SOC ≤45nm.

3. The graphite material according to any one of claims 1 to 2, characterized in that: 20nm≤Lc 100%SOC ≤60nm, optionally, 28nm≤Lc 100%SOC ≤50nm.

4. The graphite material according to any one of claims 1 to 3, characterized in that: The gram capacity of the graphite material is 280 mAh / g-340 mAh / g, and can be optionally 290 mAh / g-335 mAh / g.

5. The graphite material according to any one of claims 1 to 4, characterized in that: The volume distribution particle size Dv1 of the graphite material is 0.5 μm-3.1 μm, and can be 1 μm-2.5 μm; and / or, The volume distribution particle size Dv10 of the graphite material is 3 μm-6.2 μm, and can be 3.2 μm-5 μm; and / or, The volume distribution particle size Dv50 of the graphite material is 5 μm-15 μm, and can be 8 μm-12 μm; and / or, The particle size distribution (Dv90-Dv10) / Dv50 of the graphite material is 1.02-1.57, and can be optionally 1.11-1.

49.

6. The graphite material according to any one of claims 1 to 5, characterized in that: The grain size La of the graphite material along the a-axis direction in the lithium-intercalated 0% SOC state is 0%SOC Less than or equal to 140nm.

7. The graphite material according to any one of claims 1 to 6, characterized in that: The graphitization degree of the graphite material is 70%-88%, and can be optionally 75%-85%.

8. The graphite material according to any one of claims 1 to 7, characterized in that: The tap density of the graphite material is 1.0 m 3 / g-1.3m 3 / g; and / or, The specific surface area of ​​the graphite material is 0.6 m 2 / g-2m 2 / g.

9. The graphite material according to any one of claims 1 to 8, characterized in that: The surface of the graphite material also includes a carbon layer.

10. A method for preparing a graphite material, characterized in that: The steps include: Providing coke raw materials; The coke raw material is crushed, shaped and graded to obtain a graphite precursor; The obtained graphite precursor is placed in a graphitization furnace for graphitization treatment at a preset temperature and a preset time, and then taken out of the furnace after cooling to obtain a graphite material, wherein the preset temperature is less than 3000° C. and the preset time is less than 24 hours. Wherein, the graphite material satisfies (Lc 100%SOC -Lc 0%SOC ) / Lc 50%SOC ≤0.0750, and Lc 0%SOC Less than or equal to 50nm; Lc 0%SOC It indicates the grain size of the graphite material along the c-axis direction in the lithium-embedded 0% SOC state, in nm; Lc 50%SOC It indicates the grain size of the graphite material along the c-axis direction when the lithium is inserted into the 50% SOC state, in nm; Lc 100%SOC It represents the grain size of the graphite material along the c-axis direction in the lithium-intercalated 100% SOC state, in nm.

11. The preparation method according to claim 10, characterized in that: The graphitization furnace is a continuous graphitization furnace; and / or, The preset temperature is 2500°C-2800°C, and can be optionally 2500°C-2750°C; and / or, The preset time is 6h-18h, and can be optionally 8h-15h.

12. The preparation method according to any one of claims 10-11, characterized in that: The coke raw material includes at least one of petroleum coke and needle coke; Optionally, the coke raw material also meets the following requirements: the mass content of volatile matter is less than or equal to 10wt%, the mass content of ash is less than or equal to 0.3wt%, and the mass content of sulfur is less than or equal to 2wt%.

13. The preparation method according to claim 12, characterized in that: The coke raw material is petroleum coke, and based on the total volume of the coke raw material structure, the volume proportion of the mosaic and regional structures in the petroleum coke is greater than or equal to 60%, and can be optionally 65%-80%; or, The coke raw material is needle coke, and based on the total volume of the coke raw material structure, the volume proportion of the fiber-type structure in the needle coke is 40%-60%, and can be optionally 45%-55%.

14. The preparation method according to any one of claims 10 to 13, characterized in that: In the step of crushing, shaping and classifying the coke raw material to obtain a graphite precursor, The volume distribution particle size Dv1 of the obtained graphite precursor is greater than or equal to 0.3 μm, and can be selected to be 0.3 μm-1.4 μm; and / or, The volume distribution particle size Dv10 of the obtained graphite precursor is greater than or equal to 2.0 μm, and can be selected to be 2.1 μm-4.0 μm; and / or, The volume distribution particle size Dv50 of the obtained graphite precursor is 5 μm-16 μm, and can be 8 μm-11 μm; and / or, The particle size distribution (Dv90-Dv10) / Dv50 of the obtained graphite precursor is 1.05-1.61, and can be optionally 1.18-1.

52.

15. The preparation method according to any one of claims 10 to 14, characterized in that: Before placing the obtained graphite precursor in a graphitization furnace for graphitization treatment at a preset temperature and a preset time, the method further includes the steps of: pre-carbonizing the obtained graphite precursor; Optionally, the obtained graphite precursor is heated to 600° C.-1100° C. at a heating rate of 1° C. / min-5° C. / min and kept at this temperature for 18 h-24 h for pre-carbonization treatment.

16. The preparation method according to any one of claims 10 to 15, characterized in that: The preparation method further comprises the steps of placing the obtained graphite precursor in a graphitization furnace for graphitization treatment at a preset temperature and a preset time, and then screening and removing magnetism to obtain a graphite material.

17. The preparation method according to any one of claims 10 to 16, characterized in that: The preparation method further comprises the steps of: mixing the obtained graphite material with the coating agent and placing the mixture in a carbonization furnace for carbonization treatment to form a carbon layer on the surface of the graphite material; Optionally, the coating agent includes asphalt, and more preferably, the softening point temperature of the asphalt is 150°C-300°C, and optionally 200°C-250°C; and / or, Optionally, the temperature of the carbonization treatment is 950°C-1300°C, optionally 1100°C-1200°C; and / or, Optionally, the carbonization treatment time is 1h-5h, optionally 2h-3h.

18. A negative electrode sheet, comprising a negative electrode current collector and a negative electrode film layer located on at least one surface of the negative electrode current collector, characterized in that: The negative electrode film layer comprises the graphite material according to any one of claims 1 to 9 or the graphite material prepared by the preparation method according to any one of claims 10 to 17.

19. The negative electrode sheet according to claim 18, characterized in that: The compaction density of the negative electrode film layer is 1.15 g / cm 3 -1.55g / cm 3 and / or, The surface density of the negative electrode film layer is 7 mg / cm 2 -15mg / cm 2 .

20. A battery, characterized in that: Comprising the negative electrode sheet as described in any one of claims 18-19.

21. An electrical device, characterized in that: The battery according to claim 20 is used to provide electrical energy.

Citation Information

Patent Citations

  • Electrochemical device

    CN113140726A

  • Negative electrode active material, and negative electrode, electrochemical device, and electronic device comprising same

    CN113795947A

  • Positive pole piece and battery

    CN115411226A

  • Secondary battery, preparation method therefor, and device comprising same

    CN116741938A

Cited By

  • Graphite material, preparation method therefor, negative electrode piece containing graphite material, battery, and electrical apparatus

    EP4819245A1